In vitro bone metastasis dwelling in a 3D bioengineered niche. (February 2021) - Han, Weijing; El Botty, Rania; Montaudon, Elodie; Malaquin, Laurent; Deschaseaux, Frederic; Espagnolle, Nicolas; Marangoni, Elisabetta; Cottu, Paul; Zalcman, Gérard; Parrini, Maria Carla; Assayag, Franck; Sensebe, Luc; et al.
Abstract: Bone is the most frequent metastasis site for breast cancer. As well as dramatically increasing disease burden, bone metastases are also an indicator of poor prognosis. One of the main challenges in investigating bone metastasis in breast cancer is engineering in vitro models that replicate the features of in vivo bone environments. Such in vitro models ideally enable the biology of the metastatic cells to mimic their in vivo behavior as closely as possible. Here, taking benefit of cutting-edge technologies both in microfabrication and cancer cell biology, we have developed an in vitro breast cancer bone-metastasis model. To do so we first 3D printed a bone scaffold that reproduces the trabecular architecture and that can be conditioned with osteoblast-like cells, a collagen matrix, and mineralized calcium. We thus demonstrated that this device offers an adequate soil to seed primary breast cancer bone metastatic cells. In particular, patient-derived xenografts being considered as a better approach than cell lines to achieve clinically relevant results, we demonstrate the ability of this biomimetic bone niche model to host patient-derived xenografted metastatic breast cancer cells. These patient-derived xenograft cells show a long-term survival in the bone model and maintain their cycling propensity, and exhibit the same modulated drug response as in vivo . This experimental system enables access to the idiosyncratic features of the bone microenvironment and cancer bone metastasis, which has implications for drug testing.